Jak wspierać wspierających? Wolontaryjny zryw społeczny na rzecz uchodźców wojennych z Ukrainy – analiza tematyczna doświadczenia wolontariatu i jej implikacje praktyczne - Sternak, Agnieszka; Przewłoka, Paweł (Kultura-Społeczeństwo-Edukacja, 2024)
The aim of the study was to learn the personal perspective of the experience of providing aid by volunteers involved in help for refugees from Ukraine who came to Polish in February 2022. The particular interest were the emotions experienced by volunteers in the circumstances of providing assistance at reception points located at railway stations in the capital of Poland, where people fleeing the war could receive support in the initial period of the invasion in Ukraine. The study was carried out in accordance with the assumptions of the phenomenological approach, which allows to describe the phenomenon by the meaning given to it by the respondents. The data collected was compiled with thematic analysis techniques. As a result, ten topics were distinguished, including: experiences related to the war and volunteer activities, the image of Ukrainians coming to Poland, motives for taking up help and satisfaction derived from it, the importance of the support of relatives and a group of cooperating volunteers for regulating emotions accompanying volunteer activity. Participants were strongly affected by the outbreak of the war, although they differed in the intensity of their fear for Polish safety and their commitment to following information about the war. They had a positive image of Ukrainians, due to their perceived cultural similarity to Poles. Listening to the refugees’ stories was particularly emotionally difficult for those who spoke Russian. Participants felt a sense of accomplishment and satisfaction from helping. An important benefit of volunteering was the bonds with other volunteers, which also served as mutual support and a source of strategies for regulating negative emotions. The study presents examples of good practices used by Polish NGOs carrying out volunteering, as well as provides practical implications useful in planning psychological support for people helping refugees and in other areas of volunteer assistance.